Method Development and Validation of A Novel Anti-Depressant Bupropion by RP-HPLC - Kumar, Anil; Agarwal, Dilip; Bansal, Mukesh (Asian Journal of Pharmaceutical Research and Development, 2020)
A speedy, simple and precise RP-HPLC process was developed for the estimation of novel antidepressant drug bupropion with Waters X – Bridge C-18 5µm, 4.6 X 150 mm columnusing mobile phase Acetonitrile: Ammonium bicarbonate (5mM) pH-9 adjusted with 1% Ammonium hydroxide (50:50, %v/v).The flow rate was 1 ml/min and quantification was done by PDA detector at wavelength254nm.The Bupropion eluted from the column in 5.194 min. The validation was carried out in the light of ICH guidelines with respect to parameters linearity, specificity, accuracy, limit of detection (LOD) and limit of quantification (LOQ). The proposed method showed linearity in the concentration range of 50 to 250 ppm for Bupropion. The linear regression equation of Bupropion was found to be y = 6E+06x + 91344 and correlation coefficient value was found to be 0.997 indicating a high degree of linearity for the drug. The limit of detection (LOD) of bupropion was 0.5 ppm and limit of quantification (LOQ) was 2.0 ppm. The low values of %recovery and %C.V. showed that the method is precise within the acceptance limit of 5% (according to ICH guidelines).